INTENSITAS PENGHINDARAN PAJAK PADA PERUSAHAAN: DAMPAK CORPORATE SOCIAL RESPONSIBILITY DAN CORPORATE GOVERNANCE - Arwaly Haifa Salsabila; Dianwicaksih Arieftiara; Ni Putu Eka Widiastuti (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2021)
The purpose of this study is examine the influence of Corporate Social Responsibility (CSR) and Corporate Governance (CG) with proxy institusional ownership and audit quality. In this research leverage and sales growth used as variabele control. The population of this research is sub-sector trade, service and investastation firms that listed in Indonesian Stock Exchange period 2016-2018. Sample selected by purposive sampling method with certain criteria and collected 172 data samples.  Testing the hypothesis in this study used Multiple Linear Regression Analysis. The result of these test indicate that: there is no significant influence of corporate social responsibility on tax avoidance, institusional ownesrship there is a positive significant on tax avoidance, audit quality there is no significant on tax avoidance.